Epidemiology of major depressive disorder in Iran: A systematic review and meta-analysis - Behnam Sadeghirad; Ali-Akbar Haghdoost; Masoumeh Amin-Esmaeili; Esmaeil Shahsavand Ananloo; Padideh Ghaeli; Afarin Rahimi-Movaghar; Elham Talebian; Ali Pourkhandani; Ahmad Ali Noorbala; Esmat Barooti (International Journal of Preventive Medicine, 2010)
Objectives: There are a large number of primary researches on the prevalence of major depressive disorder (MDD) in Iran; however, their findings are varied considerably. A systematic review was performed in order to summarize the findings. Methods: Electronic and manual searches in international and Iranian journals were conducted to find relevant studies reporting MDD prevalence. To maximize the sensitivity of the search, the references of relevant papers were also explored. We explored the potential sources of heterogeneity such as diagnostic tools, gender and other characteristics using meta-regression model. The com-bined mean prevalence rates were calculated for genders, studies using each type of instruments and for each province using meta-analysis method. Results: From 44 articles included in the systematic review, 24 reported current prevalence and 20 reported lifetime prevalence of MDD. The overall estimation of current prevalence of MDD was 4.1% (95% CI: 3.1-5.1). Women were 1.95 (95% CI: 1.55-2.45) times more likely to have MDD. The current prevalence of MDD in urban inhabitants was not significantly different from rural inhabitants. The analysis identified the variations in diagnostic tools as an important source of heterogeneity. Conclusions: Although there is not adequate information on MDD prevalence in some areas of Iran, the overall current preva-lence of MDD in the country is high and females are at the greater risk of disease.